The reproduction of life death : Derrida's La vie la mort - McCance, Dawne, 1944- (Fordham University Press, 2019)
Based on archival translations of Derrida's as-yet untapped (1975-76) La vie la mort seminar, McCance's Derrida and life death offers an unprecedented study of Derrida's engagement both with the logic of reproduction held by 1970s molecular biology and genetics and with reproductivity as theorized and performed by Freud in Beyond the Pleasure Principle.